A Lexical Analysis of Zechariah 6:1-8 - Philip Suciadi Chia; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
Zechariah 1:1-6 summarizes a speech to the people that reports the failure of the previous generations to heed the message of the prophets who God has sent while successfully challenging the current generation to turn to YHWH. The eight visions of the second block (1:7-6:15) share common compositional elements, but they also show evidence of later reworking. The third block, Zechariah 7-8, constitutes a collection of short sayings dated approximately two years after temple construction began. Zechariah 6:1-8 could be divided into two sections. First is disclosure of the vision (6:1-4) and the last one is the disclosure and explanation of the vision (6:5-8). Particularly, in this first subparagraph, Zechariah seems to present his thoughts in chiasmus. This chiasmus has a structural function which often a chiastic couplet is used to both open and close a stanza or poem. Zechariah introduced his eighth vision with four verbs, which are thematic words.